Institutional Quilombos? Black Studies in Brazil and the United States - (:unkn) unknown (My University, 2012)
The literature on Black Studies, Afro-Brazilian Studies and Comparative Race Relations between Brazil and the United State has been dedicated to the study of Black activism and education. However, there is a gap in comparative studies focused on Black Studies units in the United States and Afro-Brazilian studies in Brazil. The dissertation “Institutional Quilombos? Black Studies in Brazil and the United States” investigates how Black Studies centers and departments in Brazil and the United States exist, survive and act politically as educational and anti-racist spaces in six different institutions: the University of Wisconsin – Milwaukee; Harvard University; Temple University; the University of Brasilia (Universidade de Brasilia); the Federal University of Bahia (Universidade Federal da Bahia); the Federal University of Parana (Universidade Federal do Parana). The research is based on a web-based survey about Black Studies in Brazil, maps of Black Studies units in Brazil and the United States, and in-depth interviews of 25 professors. Relying on these interviews, the dissertation examines debates about the identity of Black Studies units, institutional racism in universities, and Black Studies units solutions to the challenge of being a Black space within predominantly white universities. Finally, I discuss the concept of an institutional quilombo as a goal of Black Studies.
Keywords: Afro-Brazilian Studies; Black Studies; Institutional Quilombo; Universities